Do higher levels of education and skills in an area benefit wider society? - John V. Winters (IZA World of Labor, 2015)
Formal schooling increases earnings and provides other individual benefits. However, societal benefits of education may exceed individual benefits. Research finds that increased average education levels in an area are correlated with higher earnings, even for locals with relatively little education. Science, technology, engineering, and mathematics (STEM) graduates appear to have especially strong external effects, due to their role in stimulating innovation and economic growth. Several strategies to test for causality find human capital externalities do exist.
Keywords: J2; R2; I2; 330; human capital; education; schooling; externalities; earnings; employment